Free trade agreements: the backbone of modern trade: Acuerdos de libre comercio: la columna vertebral del comercio moderno - Murillo Castro, Dario Fernando (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2025)
Free Trade Agreements (FTAs) are now the norm in global trade. Economic liberalization has passed by past protectionist trends. FTAs shape global governance, policies, and international relations. This study examines how contemporary trade deals exist as governance mechanisms, rather than economic facilitators. The study provides a thematic literature review of the multifaceted relationships between economics, politics, and institutional power using secondary data. The methodology will entail qualitative synthesis, which will involve comparison of the findings of existing scholarly and policy materials. This is to determine the scope of impact of FTAs on contemporary trading systems and rule-making. The distribution of trade power and form has been changed by fragmented governance and emergence of mega-regionals like CPTPP and RCEP (Rimmer, 2024). The question that guides the research is as follows: how far FTAs determine and maintain the contemporary trade system? It supposes that FTAs widen the current trade flows and reorganize the world power relations.